EFFECTIVE STRATEGIES TO IMPROVE STUDENT WRITING SKILLS - Amelia Putri Tambunan; Ayuzza Bintang Kesuma, Fayyi Fawwaz Tammir, Josua Pebriano Lumban Gaol, Sultan Ahmad Al Fatah (International Journal of Teaching and Learning, 2025)
This research aims to looking at effective strategies to improve writing skills. This research answers the research questions about the student ability in writing. Writing skills are one of the Indonesian language skills that elementary school students must master. Writing skills are the skill of expressing ideas, notions, feelings in the form of written language so that other people who read can understand the contents of the writing well. Writing is very important for students because Writing trains students to select the most relevant material or data or findings to present. Writing trains students to abstract reality or concrete data into scientific statements. Writing gets students used to reconstructing their findings or ideas into thoughts that are easier to understand. That is why every student must have good writing skills. In this research we will discuss the most effective strategies for improving students' writing skills. We use descriptive qualitative research methods because we present the data as it is without manipulation or other treatments. The aim of this research is to present a complete picture of an event or is intended to expose and clarify a phenomenon that occurs.